“Antarctic on fire”: Paleo-wildfire events associated with volcanic deposits in the Antarctic Peninsula during the Late Cretaceous - Manfroi, Joseline; Trevisan, Cristine; Dutra, Tânia Lindner; Jasper, André; Carvalho, Marcelo De Araujo; Aquino, Francisco Eliseu; Leppe, Marcelo (Frontiers in Earth Science, 2023)
The occurrence of paleo-wildfire events during the Campanian age, Late Cretaceous, is demonstrated in this study for the first time for deposits of the King George Island, South Shetland Islands, Antarctic Peninsula. Aiming to provide information that fills important paleoenvironmental and paleobiogeographic gaps about the end of the Cretaceous for the Gondwana. Samples of macroscopic charcoal were collected at two different volcanic levels of the Price Point outcrop, King George Island, during the expeditions to the Antarctic Peninsula of the Brazilian Antarctic Program (PROANTAR). The samples of charcoal were treated and later analyzed under a stereomicroscope and scanning electron microscope. The analysis allowed identifying morphoanatomical structures with potential taxonomic affinity with Podocarpaceae. These conifers were important in temperate forests of the high-latitude environments during the Late Cretaceous, and is in accordance with previous palaeobotanical records from Price Point. The analysis also showed that southern paleofloras were subject to the occurrence of paleo-wildfires fires much more frequently than previously thought. This indicates that fire and active volcanism were significant modifiers of the ecological niches of austral floras, because even in distal areas, the source of ignition for forest fires often came from the contact with a hot volcanic ash cloud where the vegetation was either totally or partially consumed by fire.